Analysis Room Scope and Draft Base in Implementation Education Citizenship - Maghfira Izzati (International Journal of Students Education, 2024)
Objective this study is for serve draft base education citizenship and understand its important role in shaping consciousness citizenship and character nation, student PGSD also need keep going develop self and increase competence in providing religious and civic education which relevant with need era. Integration technology information and communication (ICT) in learning to be one strategy the important one in increase effectiveness process learning. Student PGSD need capable integrate various technology and media learning for create atmosphere learn that interactive and inspirational for student. Study use method studies literature for explore room scope and draft base education citizenship. Results analysis show importance education citizenship in form character and citizenship identity which strong and tough for individual and nation. In conclusion, education citizenship is not only a subject at school, but also an effort systematic and integrated in build a foundation nationality which sturdy. The importance of implementing pancasila values as a basis countries, as well as understanding global issues and human rights are the focus important in forming an inclusive and modern sense of citizenship.